Personalizing the approach to asthma treatment. Issue 5 (3rd September 2018) - Ferrando, Matteo; Bagnasco, Diego; Heffler, Enrico; Paoletti, Giovanni; Passalacqua, Giovanni; Puggioni, Francesca; Canonica, Giorgio Walter
ABSTRACT: Introduction : Personalized/precision medicine has changed the vision of respiratory diseases. Asthma is now recognized as a heterogeneous disease with different pathogenic mechanisms, clinical course, and different responses to different treatments. Areas covered : According to this vision, the prescription of treatments has become more tailored. Taking into account the clinical and molecular phenotypes and endotypes, the focus has moved to the predominant characteristics of the inflammatory process, the clinical aspects, and the study of the biological mechanisms. Eventually, researchers highlighted the presence and the etiological dignity of treatable traits defined as therapeutic targets identified by specific phenotypes or endotypes through validated biomarkers. Expert commentary : All these aspects involve a novel approach, with a 'point-of-care' assessment, that seems to be more and more central to warrant a forward-step to the personalization of asthma treatment. The availability of portable, hand-held devices to assess specific biomarkers, represents an additional advantage.